2017
DOI: 10.1182/bloodadvances.2017008342
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived antibody recognizes a unique CD43 epitope expressed on all AML and has antileukemia activity in mice

Abstract: Key Points AT1413 is a monoclonal antibody isolated from a cured patient with AML that recognizes CD43s, a novel epitope expressed by AML and MDS blasts. AT1413 eliminates CD43s-expressing leukemic blasts in vitro and in vivo and may have potential as a therapeutic antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…27 Immunologic consolidation can be effective when newly infused donor immune cells that are naive with regard to the patient's AML elicit a GvL response independent of HLA-related antigen presentation, for example, to targets that are expressed on the membrane of AML blasts. 28,29 Thus, as also suggested by other studies, immunological consolidation is of importance for survival in this setting. GvHD occurred in some but not all surviving patients suggesting that immunologic consolidation can also be effective when it does not lead to GvHD.…”
Section: Discussionsupporting
confidence: 65%
“…27 Immunologic consolidation can be effective when newly infused donor immune cells that are naive with regard to the patient's AML elicit a GvL response independent of HLA-related antigen presentation, for example, to targets that are expressed on the membrane of AML blasts. 28,29 Thus, as also suggested by other studies, immunological consolidation is of importance for survival in this setting. GvHD occurred in some but not all surviving patients suggesting that immunologic consolidation can also be effective when it does not lead to GvHD.…”
Section: Discussionsupporting
confidence: 65%
“…58 Consistently, a recent study showed that patient-derived antibody recognizes a unique CD43 epitope expressed on all AML and has antileukemia activity in mice. 59 However, the mechanism of the coexpression CD5 and CD43 in the initiation, progression, and maintenance of DLBCL is currently unknown and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we have examined whether patients with AML successfully treated with allogeneic HSCT generate AML-specific antibodies (7)(8)(9). Allogeneic HSCT can evoke an immunotherapeutic graft-versus-leukemia reaction, which includes a B-cell response and the generation of tumor-specific antibodies (10).…”
Section: Introductionmentioning
confidence: 99%